EPISTEMOLOGI REVOLUSI ILMIAH THOMAS KUHN DAN RELEVANSINYA BAGI STUDI AL-QUR'AN - Afriadi Putra (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
Through his magnum opus, The Structure of Scientific Revolutions, Thomas Kuhn formed an idea of scientific development framework throughout the shifting paradigm by its stage and hierarchy that are capable to revolutionize history and philosophy of science. This scientific development's model that Kuhn presented is important espe• cially when it is placed in epistemological outline, therefore to find its relevance in various scientific fields, as well as in Islamic sciences. In Quranic studies for example, Kuhn's theory could be converted into a theoretical frame to analyze shifting paradigm of Quranic interpretation from various periods. This writing in particular examines this issue, i.e. the relevance ofThomas Kuhn's scientific revolution's theory in Quranic studies. The early assumption of this study is that the Quranic interpreters definitely employ paradigm intheir analysis, because it is inherently in their interpretation theory, intentionally or not, be used in constructing an interpretation.